The Influence of Product Quality and Price on Hebel Purchase Decision - Siahaan, Matdio; Rely, Gilbert (Dinasti International Journal of Economics, Finance & Accounting, 2024)
We often see the use of Hebel as a building wall, especially nowadays, because it is large and light, so the building can be completed more quickly. So product quality is a very important point in making consumer purchasing decisions, if the product offered is of good quality it can build consumer confidence regarding the product purchased. Another factor that can increase purchasing decisions is price. This research aims to determine the level of quality of Hebel products and prices on purchasing decisions at the Sinar Mega Tambun Selatan Building Store, Bekasi. This research uses a non-probability sampling method, namely a saturated sample with a sample of 81 respondents and also uses the help of the SPSS application program. The analysis techniques used are validity test instruments, reliability tests, classical assumption tests, multiple regression tests, t tests, F tests, coefficient of determination tests. Partial results on consumer satisfaction can be seen from the significant t value of 0.00 < 0.05 and price has a partially significant positive influence on purchasing decisions at Sinar Mega, this can be seen from the significant t value equal to 0.00 < 0.05, while simultaneously product quality and price have a significant influence on consumer satisfaction. This can be seen from the significant F value of 0.00 < 0.05.